Portfolio assessment as a problem based learning model to help elementary school students’ deal with Mathematics - Isnawati Isnawati; Dwi Yulianti; Siti Samhati (International Journal of Educational Studies in Social Sciences (IJESSS), 2021)
The concern in this study is children's inability to solve primary school math problems, with a goal to establish how students' capacity to solve mathematical problems in primary school and to describe the best method or learning model for delivering materials for the circumference and area of parallelograms and triangles using a problem-based learning model with portfolio assessment. This studi is qualitative in nature, employing a total of 30 elementary school chosen through a random sampling technique. The results showed that the problem based learning model based on the portfolio assessment was suitable for use in elementary school mathematics learning compared to conventional learning approaches because students were more active in participating in learning and the teacher was only a facilitator.